Analisis Strategi Pemeliharaan Mesin HP DesignJet Z6810 menggunakan Reliability Centered Maintenance (RCM) - Rifki Nasrullah (Widyatama University, 2026)
This study aims to analyze the maintenance strategy of the HP DesignJet Z6810 machine at PT XYZ using the Reliability Centered Maintenance (RCM) method to improve machine reliability and reduce downtime. The study was conducted through field observations, interviews, and analysis of historical damage data. The methods used include identification of critical components, analysis of Failure Modes and Effects Analysis (FMEA), and calculation of reliability indicators in the form of Mean Time Between Failure (MTBF), Mean Time to Repair (MTTR), and Availability. The results of the study indicate that Flex Cable Data and Flex Cable Print Head are the most critical components with Risk Priority Number (RPN) values ​​of 378 and 240, respectively. The initial condition of the machine has an MTBF value of 1,233 hours, MTTR of 38.25 hours, and Availability of 96.99%. The implementation of the RCM strategy through time-based preventive maintenance on critical components and Condition-Based maintenance on supporting components is projected to increase MTBF to 3,275 hours, reduce MTTR to 10 hours, and increase Availability to 99.69%. The results of the study show that the implementation of RCM can improve machine reliability, reduce the frequency of breakdowns, and support the smooth running of the production process at PT XYZ.